Fishing, fish consumption, urbanism and migrants at Tel Bet Yerah, 3200–2700 BC. (August 2021) - Lernau, Omri; Shapiro, Jamie; Paz, Sarit; Greenberg, Raphael
Abstract: Abstract : The role and significance of fish and fishing in the ancient Near East has been little studied. A new assemblage of fish remains and fishing gear recovered from Bronze Age Bet Yerah on the Sea of Galilee, however, offers insights into the transition from village to town life, and illuminates interactions between local populations and incoming groups. The assemblage also reveals temporal and spatial variations in the utilisation of local fish resources. As the first such assemblage obtained from a systematically sampled Early Bronze Age stratigraphic sequence in the Southern Levant, it highlights the contribution of secondary food-production and -consumption activities to the interpretation of socio-cultural change.